The Interdependence of Adult Relationship Quality and Parenting Behaviours among African American and European Couples in Rural, Low‐Income Communities. Issue 3 (14th May 2015) - Zvara, Bharathi J.; Mills‐Koonce, W. Roger; Heilbron, Nicole; Clincy, Amanda; Cox, Martha J.; The Family Life Project Key Contributors; Lunkenheimer, Erika S.; Leerkes, Esther M.
<x xml:space="preserve">Abstract</x> The present study extends the spillover and crossover hypotheses to more carefully model the potential interdependence between parent–parent interaction quality and parent–child interaction quality in family systems. Using propensity score matching, the present study attempted to isolate family processes that are unique across African American and European American couples that are independent of other socio‐demographic factors to further clarify how interparental relationships may be related to parenting in a rural, low‐income sample. The Actor–Partner Interdependence Model (APIM), a statistical analysis technique that accounts for the interdependence of relationship data, was used with a sample of married and non‐married cohabiting African American and European American couples (n = 82 dyads) to evaluate whether mothers' and fathers' observed parenting behaviours are related to their behaviours and their partner's behaviours observed in a couple problem‐solving interaction. Findings revealed that interparental withdrawal behaviour, but not conflict behaviour, was associated with less optimal parenting for fathers but not mothers, and specifically so for African American fathers. Our findings support the notion of interdependence across subsystems within the family and suggest that African American fathers may be specifically responsive to variations in interparental relationship quality. Copyright © 2015 John Wiley & Sons, Ltd.